When Arrivals Turned into Refugees: Stateless Jews’ Emigration from Lithuania 1939–1940 - Venclauskas, Linas (History / Istorija, 2022)
Abstract. In the article, in addition to the already quite well-known episode of the issue of lifetime visas by the Japanese vice-consul in Lithuania Chiune Sugihara in Kaunas in the summer of 1940, Lithuania’s position on the issue of refugees is presented, as well as the efforts of Lithuanian diplomats in negotiating with the governments of Britain and the USSR about the possibilities of emigration of willing refugees – Polish Jews. The contribution of Jan Zwartendijk, Honorary Consul of the Netherlands in Lithuania, to the history of salvation is also remembered. The paths of emigration are discussed, showing their entire spectrum, and not just the usual ones with the Trans-Siberian route linked by Sugihara visas. The changing policy of the Japanese government on the issue of transit visas is reviewed.